Analisis Pengaruh Marketing Mix Dan Marketing Digital Terhadap Keputusan Untuk Menggunakan Jasa Pelayanan Pencucian Sepatu Pada Usaha Mikro Goods Care Cikarang - SJ, Mutoharoh; Hutauruk, Basar M (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Nowadays, online  purchasing decisions have become   commonplace  just like offline shopping or being slapped.  Currently,  various presentations are carried out to market products through the internet so that consumers can easily  receive existing information.  The purpose obtained in this study  is to  find out a relationship or influence of the  Marketing mix and digital marketing in sales from the Goods Care Cikarang company. The  population taken in the study was consumers who used Cikarang  Goods Care services using  research variables totaling 123 people The use of the slovin formula aims to  determine the  sizeof an A sample in this  study  with a total sample of 94 respondents.  The use of the  Structural Equation Model (SEM)  analysis  method and processing using the lisrel 8.8 application. from the results of this research test successfully concluded that the Marketing Mix did not have a  significant  influence on the decision of  a   purchasing the Cikarang Micro Goods Care business, Digital Marketing turns out to have a  significant influence on purchasing decisions in the Cikarang Micro Goods Care business, Marketing  Mix and Digital Marketing  which  we research the  significant effect on purchasing decisions in the  Cikarang Micro Goods Care business.